2018
DOI: 10.3892/mco.2018.1722
|View full text |Cite
|
Sign up to set email alerts
|

Gastric outlet obstruction caused by metastatic tumor of the stomach originating from primary breast cancer: A case report

Abstract: The most common sites of breast cancer metastasis are the bone, liver, lung and brain, while gastrointestinal metastasis from breast cancer is rare. We herein present the case of a 68-year-old woman who was admitted to our department with nausea and appetite loss. The patient's medical history included right mastectomy with sentinel lymph node biopsy 5 years earlier for invasive lobular carcinoma, measuring 6.2 cm in greatest diameter, without lymphovascular invasion. Two years after the surgery, the patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some authors reported in diagnosis of gastric metastasis the use of 18F-2-deoxy-2fluoro-D-glucose (FDG) positron emission tomography combined with computed tomography imaging that revealed FDG uptake across the thickness of the antral wall (30).…”
Section: Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported in diagnosis of gastric metastasis the use of 18F-2-deoxy-2fluoro-D-glucose (FDG) positron emission tomography combined with computed tomography imaging that revealed FDG uptake across the thickness of the antral wall (30).…”
Section: Diagnosticmentioning
confidence: 99%
“…Considering the stage of generalized disease, the current trend is to manage the complications of gastric metastasis in a minim invasive manner: endoluminal stents for gastric outlet obstruction, endoscopic or endovascular therapy for tumoral bleeding (50,71).…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…In rare cases, aggressive surgical treatment has been recommended for a solitary gastric metastasis, followed by chemotherapy and systemic treatment; such courses of treatment have shown minor benefit to overall survival [ 45 ]. Less invasive techniques should be considered, such as embolization for gastric bleeding and endoscopic stent placement for obstruction [ 46 , 47 ]. In general, the median survival of patients with metastatic breast cancer ranges between 2 and 3 years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[9] The most common malignancies causing GOO are pancreatic and gastric adenocarcinomas and less commonly from lymphomas, ampullary carcinoma, and biliary tract cancers. [10] Metastatic ILC is an uncommon cause of GOO, and only 6 cases have been reported [11][12][13][14][15][16] (see Table 1). Although ILC accounts for approximately 10% of all breast cancers, it is this subtype that accounts for more than half of the reported cases of GI tract metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of breast cancer presenting as gastric outlet obstruction. [11][12][13][14][15][16] The diagnosis of metastatic ILC, in this case, was initially elusive given the unusual presentation and the fact that the gastric mucosa at the pylorus appeared endoscopically normal. However, the clinical suspicion of malignancy was high in our differential.…”
Section: Discussionmentioning
confidence: 99%